God's Protection in the Post-Pandemic Phenomenon of Extreme Poverty in Indonesia - Dr. Suryaningsih, S.S., M.Pd.K.; Louis Cynta; Merlin Chintia Katup (PT. Penerbit Tiga Mutiara, 2024)
The Covid 19 pandemic, which has lasted for about three years, has had a significant impact on all aspects of life throughout the world, especially in Indonesia. Every day humans can move quickly and without restrictions, but during the Covid 19 pandemic human movement was limited and restricted by several rules that have been set, including the number of gatherings even in the early days of the Covid 19 pandemic, staying at home or working from home, studying Working from home is mandatory for all levels of society and groups, both in schools, campuses and offices, so that the spread of the Covid 19 virus does not become widespread. This certainly has a significant impact on the speed of the economy, finances and of course the welfare of society. Since March 2022, the poverty rate in Indonesia has increased by 9.54%, and the government is trying to create many programs to eradicate it. This research answers the question: what is meant by poverty? What are the impacts of living in poverty? What is the solution to God’s protection in the post-pandemic extreme poverty phenomenon in Indonesia? The outcomes of using the literature investigate method are listed below: (1) Poverty as a disadvantage to citizens measured in terms of a certain standard of living, which refers to relative poverty designs that carry out similar analyzes in many poor countries. (2) The consequences of living in poverty are worsening health, declining health, and lack of security. (3) Overcoming poverty by enlivening God's protection, namely God's duty to prevent many poor people from becoming protectors of lifestyles, families and church congregations like Christ.